ANALISIS KADAR UNSUR HARA MAKRO DAN MIKRO PADA DAUN KELAPA SAWIT DI DAERAH PERKEBUNAN KELAPA SAWIT RIAU - Merry Asria; Ice Armaida Safitri (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Nutrients are elements in the soil that are needed by plants to grow and develop. Macro nutrients are elements that are needed in large quantities, such as K, Mg and Ca. Micro nutrients are elements that are needed in small amounts, such as Fe and Cu. Nutrient content in palm oil leaves is used as one of the considerations in preparing fertilizer recommendations and knowing the fertility rate of oil palm plants. If nutrients are sufficient, it can increase the production of fresh fruit bunches in oil palm plants. Determination of K, Mg, Ca, Fe and Cu levels was carried out by the Atomic Absorption Spectrophotometry (AAS) method. From the research, the results of element K are deficient, the element Mg with nutrient content is 0.22 - 0.39%, the element Ca is 0.41 - 0.67%, the element Fe is 79 - 112 ppm, and the element Cu is 5 - 8 ppm.